Amp it up leading for hypergrowth by raising expectations, increasing urgency, and elevating intensity - Slootman, Frank (Hoboken, NJ Wiley, 2022)
Frank Slootman is the only CEO to take three massive companies public and has led two of the world's fastest growing enterprise tech companies of all time. In Amp It Up, Frank shares everything he's learned about what it takes to fully optimize an organization for hyper growth and scale. Broken into 20 chapters addressing the essential challenges for leaders, managers, and entrepreneurs, this book is a combination of first principles, mindsets, and tactical advice that, if embraced, will help readers unlock the true potential of their organization. Amp It Up is difficult and uncomfortable--it's about challenging the status quo every day, getting used to making conflicted trade-offs, avoiding incrementalism, refocusing resources to the only places where it counts, and being uncompromisingly objective. But its reward is great
Includes index
Keywords: Strategic planning-Goal (Psychology)